G18 Evaluation of a peer parenting support scheme for parents of disabled children. (27th April 2015) - Bray, L; Carter, B; Sanders, C; Keegan, K
Abstract : Aim: This presentation will discuss findings from a study which evaluated Scope's Face 2 Face peer parenting support scheme for parents of children with a disability or additional need within a regional children's hospital. Methods: Data were collected before and after the period of befriending from the parents providing support (befrienders) and the parents receiving support (befriendees). This was a mixed methods study. Quantitative data were collected from the administration of four structured questionnaires (GHQ-12, Paediatric Inventory for Parents, Peds QL™ Family Impact Module, Contact with Health Professionals). Qualitative data were collected during semi-structured qualitative interviews. Results: 26 befriendees (24 mothers and 2 fathers) and 13 befrienders participated in the research project. In total 72 sets of questionnaires were completed and 75 interviews were conducted. The parents in this study (befriendees and befrienders) demonstrated high levels of psychological distress (GHQ-12 scores) before befriending compared to other published parent literature. The befriendees and befrienders reported positive experiences of the scheme and this was reflected in their improved questionnaire scores for psychological wellbeing, family functioning and health related quality of life. Despite improved scores the parents continued to demonstrate poor psychological and emotional wellbeing. After the befriending experience, the befriendees reported coping better, developing a positive view of being a parent to a disabled child and feeling more able to move forwards. The befrienders described both a sense of fulfilment and worth at being able to help and support another parent and they expressed a renewed sense of well-being. Conclusion: The findings demonstrated the need to address and support the emotional wellbeing of parents with disabled children and highlights the importance of this support being delivered by other parents who 'know and have been there'. Befrienders and befriendees reported improvements in psychological well-being, family functioning and health-related quality of life.